Bahan Ajar Mata Kuliah Nahwu Awal Berbasis Pembelajaran Mikro untuk Mahasiswa Pendidikan Bahasa Arab Universitas Negeri Jakarta: Pengembangan Materi Pembelajaran Berbasis Microlearning untuk Mata Kuliah Nahwu Awal - Samsi Setiadi; Khotimatun Nafi'ah; Puti Zulharby; Yumna Rasyid; Ihwan Rahman Bahtiar (ELOQUENCE : Journal of Foreign Language, 2026)
Background: Among the branches of Arabic linguistics that students need to master is Nahwu (Arabic grammar). Online Nahwu learning has led to a learning loss phenomenon, resulting in varying levels of students’ understanding of the material. Some students in the Introductory Nahwu course have demonstrated low comprehension. This was evident when they were unable to answer questions related to the material during online class discussions. Purpose: This study aims to develop microlearning-based teaching materials for the  Nahwu Awal course as a strategic alternative to mitigate learning loss. Method: This study employed a Research and Development (R&D) design using the ADDIE model, limited to the product development stage. Data was collected from participants representing the target population through purposive sampling. The research instruments included questionnaires and observation sheets to assess product feasibility. The data were analyzed descriptively to evaluate the quality and validity of the developed product. Results and Discussion: he needs analysis showed that 66.3% of students experienced difficulties in learning Nahwu Awal. In addition, 97.5% of respondents indicated the need for visual and audiovisual microlearning-based teaching materials. The developed product was then validated by subject matter experts and media experts. The validation results indicated that the product was categorized as feasible to highly feasible for use in learning. These LMS-based microlearning teaching materials were considered effective in addressing learning needs and overcoming the limitations of engaging and interactive instructional materials. Conclusion and Implications: Students in the Nahwu Awal course need microlearning-based teaching materials that integrate visual and audiovisual content. The materials are presented as short content segments that gradually explain each learning topic in the LMS. Microlearning-based teaching materials can help overcome learning loss and support more effective learning in the Nahwu Awal course.